AN ANALYSIS OF LIBERAL FEMINISM IN THE NOTEBOOK NOVEL (1996) BY NICHOLAS SPARKS - Gunawati, Pande Made; Tantra, Dewa Komang; Juniarta, Putu Adi Krisna (International Journal of Language and Literature, 2020)
In The Notebook by Nicholas Sparks, Allison Nelson was characterized as an inspiring woman who fought for her dreams. Meanwhile, Noah Calhoun was described as a loving man that respected Allison as a woman. This novel contained traits of rich liberal feminism. The purpose of the present research was to find out the traits of Noah Calhoun and Allison Nelson as the main characters that represented liberal feminism in the novel. The method of this research was textual analysis to analyze the traits. Data collection was linguistics unit corpora recorded in written forms. The finding of this research can be stated that Noah Calhoun and Allison Nelson were categorized as liberal feminists. Their traits were a combination of positive feminine and masculine traits. The traits of the main characters as liberal feminists were appreciative, forceful, strong, devoted, firm, sensitive, confident, patient, carefree, responsible, and independent.